Comparison of Cardiovascular Risk Factors for Coronary Heart Disease and Stroke Type in Women. Issue 19 (2nd October 2018) - Leening, Maarten J. G.; Cook, Nancy R.; Franco, Oscar H.; Manson, JoAnn E.; Lakshminarayan, Kamakshi; LaMonte, Michael J.; Leira, Enrique C.; Robinson, Jennifer G.; Ridker, Paul M; Paynter, Nina P.
Abstract : Background: Cardiovascular risk factors have differential effects on various manifestations of cardiovascular disease, but to date direct formal comparisons are scarce, have been conducted primarily in men, and include only traditional risk factors. Methods and Results: Using data from the multi‐ethnic Women's Health Initiative Observational Study, we used a case–cohort design to compare 1731 women with incident cardiovascular disease during follow‐up to a cohort of 1914 women. The direction of effect of all 24 risk factors (including various apolipoproteins, hemoglobin A1c, high‐sensitivity C‐reactive protein, N‐terminal pro‐brain natriuretic peptide, and tissue plasminogen activator antigen) was concordant for coronary heart disease (CHD, defined as myocardial infarction and CHD death) and ischemic stroke; however, associations were generally stronger with CHD. Significant differences for multiple risk factors, including blood pressure, lipid levels, and measures of inflammation, were observed when comparing the effects on hemorrhagic stroke with those on ischemic outcomes. For instance, multivariable adjusted hazard ratios per standard deviation increase in non–high‐density lipoprotein cholesterol were 1.16 (95% confidence interval, 1.06–1.28) for CHD, 0.97 (0.88–1.07) for ischemic stroke, and 0.76 (0.63–0.91) for hemorrhagic stroke ( P <0.05 for equal association). Model discrimination was better for models predicting CHD or ischemic stroke than for models predicting hemorrhagic stroke or a combined end point. Conclusions: Cardiovascular risk factors have largely similar effects on incidence of CHD and ischemic stroke in women, although the magnitude of association varies. Determinants of ischemic and hemorrhagic stroke substantially differ, underscoring their distinct biology. Cardiovascular disease risk may be more accurately reflected when combined cardiovascular disease or cerebrovascular outcomes are broken down into different first manifestations, or when restricted to ischemic outcomes.